Long-term antibody persistence and exceptional vaccination response on previously SARS-CoV-2 infected subjects. Issue 31 (13th July 2021) - Ferrari, Davide; Di Resta, Chiara; Tomaiuolo, Rossella; Sabetta, Eleonora; Pontillo, Marina; Motta, Andrea; Locatelli, Massimo
Abstract: Background: The first COVID-19 vaccines are being distributed to the general population. However, the shortage of doses is slowing down the goal of reaching herd immunity. The aim of the study was to verify whether previously SARS-CoV-2 infected subjects, a considerable portion of the population, should receive the same vaccination treatment of seronegative individuals. Methods: Health-professionals either recovered from COVID-19 or never infected by SARS-CoV-2 were serologically tested at different time-points right before, and several days after, vaccination. Results: Previously infected individuals showed humoral immune responses, 21 days after the first dose, that was approximately 10-folds higher than the seronegative group 21 days after the second dose. Seropositivity persists for at least 11 months. Conclusion: During a shortage of COVID-19 vaccine doses, previously SARS-CoV-2 infected individuals should be dispensed from the vaccination campaign. When dose availability returns to normality, injection of a single dose for seropositive individuals should be considered.